Clinical effectiveness of selective nerve root block in lumbar radiculopathy - Singh, Atul; Mallick, Tanmay; Singh, Sarvesh Kumar; Abrol, Ajay (International Journal of Research in Orthopaedics, 2021)
Background: Epidural steroid injections (ESIs) have been used as an adjunct in the treatment of sciatica. Since the early reports, success rates ranging from 18% to 90% (average, 67%) have been documented. However, the efficacy of ESI has lasted, on the average, less than 3 months. Methods: This study was conducted at Abrol medical centre, Punjab from June 2019 to June 2020. One hundred patients with back pain documented with lumbar disc disease treated initially with rest, analgesics and physiotherapy for at least six weeks were included in the study and treated with transforaminal epidural steroid injection. The protocol of the study was approved by ethical committee. Patients to be participated in this study were documented. Patients with lumbar disc disease were given transforaminal epidural steroid injection in Orthopaedics operation theatre of our institute. Informed and written consent were obtained as per ethical committee guidelines. Results: Pre-procedure Roland Morris disability mean score was 17.54 and it got reduced to 5.57 by 4th day immediately post injection, was 6.44 by 6 weeks, by 3rd month 7.1 and by end of 6 months it was 8.34. Improvement in score on 4th day post injection was 68.24 percent which is considered significant and successful. Conclusions: Transforaminal epidural steroid treatment better medication for pain relief, patient satisfaction, disability improvement and functional improvement.